Exploring Green industrial policy in South Africa through the lens of vertically specialized industrialization - Murray, David (Energy Research Centre, 2018)
Through various policy mechanisms deployed in the last seven years, the South African government has pursued the localization of renewable energy manufacturing. These efforts are related to the Department of Trade and Industry's broader goals to industrialize the South African economy by increasing the range and value-add of domestically manufactured products. This thesis uses global value chain analysis to determine what ways local wind and solar manufacturing firms relate to this goal by pursuing innovation, upgrading, workforce development, and regional market penetration strategies. The author uses the theoretical framework of Vertically Specialized Industrialization (VSI) as outlined by Milberg, Jiang, and Gereffi as the basis for assessing firm-level governance strategies. The research was performed through semi-structured telephonic interviews with senior level staff at renewable energy firms and non-governmental organizations, as well as a review of public reports. The findings revealed that wind and solar firms are not significantly pursuing upgrading or innovation strategies as associated with VSI. This is likely the result of insufficient market demand and policy incentives, as well as competition from countries with comparative advantage.